1994
DOI: 10.1161/01.hyp.23.1_suppl.i93
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of response to neuropeptide Y in the nucleus tractus solitarius of spontaneously hypertensive rats.

Abstract: In normotensive rats, microinjections of neuropeptide Y (2.5 to 25 ptnol) into the unilateral nucleus tractus solitarius elicited dose-dependent vasodepressor and bradycardic responses accompanied by an inhibition of sympathetic nerve firing. After microinjections of the a 2 -adrenergic receptor antagonist yohimbine (100 ng) into the nucleus tractus solitarius, the depressor and bradycardic responses to the injection of neuropeptide Y (25 pmol) into the nucleus tractus solitarius were significantly attenuated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The depressor effect of Int NPY was significantly reduced when examined in 10-week-old SHR in contrast to WKY, Sprague Dawley or DOCA-salt hypertensive rats [69]. Injections of NPY into the NTS also induced a depressor effect that was also attenuated in SHR compared to WKY [72].…”
Section: Functional Npy Responsivenessmentioning
confidence: 86%
“…The depressor effect of Int NPY was significantly reduced when examined in 10-week-old SHR in contrast to WKY, Sprague Dawley or DOCA-salt hypertensive rats [69]. Injections of NPY into the NTS also induced a depressor effect that was also attenuated in SHR compared to WKY [72].…”
Section: Functional Npy Responsivenessmentioning
confidence: 86%
“…The arcuate nucleus sends efferent projections that contain NPY to many nuclei involved in autonomic regulation, such as the PVN and NTS (44, 45). Within the PVN and NTS, NPY has direct and indirect effects on blood pressure (46–49). Moreover, the NPY system appears to be dysfunctional in SHR in these same regions, particularly in the NTS (32,47–50), suggesting that increased prepro‐NPY mRNA expression in the arcuate nucleus may contribute to neurochemical and functional deficits in regions implicated in cardiovascular control.…”
Section: Discussionmentioning
confidence: 99%
“…However, the present study has shown that chronic restraint induced a significant increase in prepro‐NPY mRNA expression in the NTS of SHR, while the expression of prepro‐NPY mRNA did not differ from basal levels in WKY rats exposed to chronic restraint. The implications of an increased expression of prepro‐NPY mRNA in the NTS are widespread, as microinjection of NPY into the NTS has resulted in hypotension, bradycardia, bradypnea and elevated plasma insulin levels (48, 49, 62–64). Furthermore, strain‐related differences in NPY neurochemistry and functional effects of NPY have been reported in the NTS of SHR compared to WKY (32).…”
Section: Discussionmentioning
confidence: 99%